Self‐Formed Protection Layer on a 3D Lithium Metal Anode for Ultrastable Lithium–Sulfur Batteries. Issue 10 (12th April 2019) - Yan, Xinxiu; Zhang, Huan; Huang, Meiling; Qu, Meizhen; Wei, Zhikai
Abstract: Lithium metal anodes are a key component of high‐energy‐density lithium–sulfur (Li–S) batteries. However, the issues associated with lithium anodes remain unsolved owing to the immature lithium anode construction and protection technology, which leads to internal short circuits, poor capacity retention, and low coulombic efficiency for high‐sulfur‐loading Li–S batteries. Herein, a highly stable 3D lithium carbon fiber composite (3D LiCF) anode for high‐sulfur‐loading Li–S batteries was demonstrated, in which a self‐formed hybrid solid‐electrolyte protection layer was constructed on a lithium metal surface through codeposition of thiophenolate ions and inorganic lithium salts by using diphenyl disulfide as a co‐additive in the electrolyte. The aromatic components from thiophenolate could improve the stability of the protection layer, and the 3D structure of the carbon fiber could effectively buffer the volume effect during lithium cycling. A Li–S battery based on a 3D LiCF anode exhibited excellent cycling stability with an energy efficiency of 89.2 % for 100 cycles in terms of a high energy density of 22.3 mWh cm −2 (10 mAh cm −2 area capacity of lithium cycling). This contribution demonstrates versatile and ingenious strategies for the construction of a 3D lithium anode structure and protection layer, providing an effective solution for practical stable Li–S batteries. Abstract : A 3D lithium carbon fiber composite anode with a self‐formed protection layer is constructed through codeposition of thiophenolate ions and inorganic lithium salts by using an electrolyte containing diphenyl disulfide and LiNO3 . When coupled with a high‐sulfur‐loading cathode, the lithium–sulfur batteries exhibit ultrastable electrochemical performance.